Estimating regions of air trapping from electrical impedance tomography data. (31st May 2018) - Mueller, Jennifer L; Muller, Peter; Mellenthin, Michelle; Murthy, Rashmi; Capps, Michael; Alsaker, Melody; Deterding, Robin; Sagel, Scott D; DeBoer, Emily
Abstract: Objective : Electrical impedance tomography (EIT) has been shown to be a viable non-invasive, bedside imaging modality to monitor lung function. This paper introduces a method for identifying regions of air trapping from EIT data collected during tidal breathing and breath-holding maneuvers. Approach : Ventilation–perfusion index maps are computed from dynamic EIT images. These maps are then used to identify regions of air trapping in the area of the lung as regions that are poorly ventilated but well perfused throughout the breathing and cardiac cycles. These EIT-identified regions are then compared with independently identified regions of low attenuation, or air trapping, on chest CT. Results of this method are demonstrated in two children with cystic fibrosis and on a healthy control subject. Main results : In both CF children, the EIT-identified regions of air trapping matched the regions indicated from the chest CT. The EIT-based method is only validated with CT scans within 4 cm of the chest cross-section defined by the electrode plane. Significance : The results indicate the potential use of EIT-derived ventilation–perfusion index maps as a non-invasive method for identifying regions of air trapping.